2022
DOI: 10.1002/we.2715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blade structural and aerodynamic uncertainties on wind turbine loads

Abstract: Offshore wind power has been in the spotlight among renewable energy sources. The current trends of increased power ratings and longer blades come together with the aim to reduce energy costs by design optimisation. The standard approach to deal with uncertainties in wind‐turbine design has been by the use of characteristic values and safety factors. This paper focusses on modelling the effect of structural and aerodynamic uncertainties in blades. First, the uncertainties in laminate properties are characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The excellent agreement of the pressure distributions on the wing demonstrates the preservation of the cloud geometry. Except at the root and tip, the observed differences between the chord lengths of the three blades were within the ±1% standard tolerances (IEC 61400-22) mentioned by [11]. The latter also observed 2% to 4% differences in the lift coefficient, while polars calculated for this study showed lift differences of 0.1.…”
Section: Resultssupporting
confidence: 78%
“…The excellent agreement of the pressure distributions on the wing demonstrates the preservation of the cloud geometry. Except at the root and tip, the observed differences between the chord lengths of the three blades were within the ±1% standard tolerances (IEC 61400-22) mentioned by [11]. The latter also observed 2% to 4% differences in the lift coefficient, while polars calculated for this study showed lift differences of 0.1.…”
Section: Resultssupporting
confidence: 78%
“…Due to their large size and the low level of automation in the manufacturing process, finished rotor blades have a relatively high level of structural uncertainty. These uncertainties include manufacturing defects, positional alignment errors, and material property uncertainties [2].…”
Section: Introductionmentioning
confidence: 99%
“…The face sheets' material distributions are completely uncorrelated, allowing for both local and global asymmetry. The results are discussed in comparison to the standard deviation of the material properties, which was taken from the work of Gonzaga et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbine blades possess a complex geometry optimised for aerodynamic efficiency [12] and structural integrity [13]. Among the various manufacturing techniques employed, vacuum-assisted resin transfer moulding is widely used to produce longer blades exceeding 55 meters in length.…”
Section: Introductionmentioning
confidence: 99%